Relationship between Financial Liberalization and Economic Growth in Emerging Economies: The Case of Vietnam - Tran, Huy Hoang (University of Economics Ho Chi Minh City, 2023)
This paper examines the process of financial liberalization in Vietnam over the period from 1993 to 2013. On adopting Vector Error Correction Model (VECM), the results suggest that there is a long-term relation between economic growth and financial liberalization, in which the financial market liberalization and financial services liberalization provide better support during the growth of Vietnam’s economy. In addition, using various techniques including Granger causality test, impulse response analysis, and variance decomposition, the paper also clarifies the motives for financial liberalization from the process of short-term financial development and economic growth in the country.